Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Pada BPPSDMP Kementerian Pertanian Jakarta - Lola Yolanda; Rani Kurniasari (Institut Nalanda, 2023)
This study was conducted with the aim of knowing and analyzing the influence of the work environment and work motivation partially and simultaneously on employee performance at the BPPSDMP of the ministry of agriculture. The data collection method in this study was carried out by distributing questionnaires to 48 respondents, then the sampling technique used in this study used saturated samples. The scale used in this study is the Likert scale. The data source is obtained using primary data and secondary data. Primary data were obtained through the distribution of questionnaires to BPPSDMP employees of the ministry of agriculture. While secondary data is obtained through books and journals related to research. This research was assisted by SPSS software for windows. Based on the results of the study, it shows that the environment has a positive and significant effect on employee performance at the BPPSDMP of the ministry of agriculture because the calculated t value is greater than the table t with a value of 8.277 > 1.679 and a sig value of 0.000 < 0.05 which can be concluded The environment has a positive and significant effect on employee performance at the BPPSDMP of the ministry of agriculture. While the results of the calculation of the work motivation variable obtained the results of the t test The Effect of Work Motivation on Employee Performance is known t calculate the < t table, namely – 5.407 < 1.679 and the sig value of 0.000 < 0.05 which can be concluded Motivation has a negative and significant influence on Employee Performance at the BPPSDMP of the Ministry of Agriculture. Work Environment and Work Motivation have a positive and significant effect on employee performance as shown from the results of F values calculated 36.808 > 3.20 and sig values. 0.000 < 0.05 which can be concluded Work Environment and Work Motivation have a positive and significant effect on Employee Performance at BPPSDMP Ministry of Agriculture.